2008
DOI: 10.1016/j.ejheart.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of endothelial dysfunction are elevated and related to prognosis in chronic heart failure patients with diabetes but not in those without diabetes

Abstract: Background: Biomarkers of endothelial dysfunction, such as soluble E-selectin, and von Willebrand factor (vWf) are elevated in patients with chronic heart failure (CHF). The impact of diabetes mellitus (DM) on these biomarkers, and their relation to prognosis remains unknown. Aims: to investigate the impact of DM on plasma levels and the prognostic value of E-selectin and vWf in patients with CHF. Methods and results: Plasma levels of E-selectin and vWf were measured in 195 CHF patients with (n = 48, 24.5%), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Kistorp et al [43 ] have prospectively studied during a median of 2.5 years whether albuminuria and other biomarkers of endothelial dysfunction at baseline are related to prognosis in patients with heart failure with and without diabetes. The authors found that among the diabetic heart failure patients albuminuria, plasma Eselectin and fasting blood glucose predicted the risk of ischemic events, but this association was not observed in nondiabetic heart failure patients.…”
Section: Albuminuria In Patients With Established Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Kistorp et al [43 ] have prospectively studied during a median of 2.5 years whether albuminuria and other biomarkers of endothelial dysfunction at baseline are related to prognosis in patients with heart failure with and without diabetes. The authors found that among the diabetic heart failure patients albuminuria, plasma Eselectin and fasting blood glucose predicted the risk of ischemic events, but this association was not observed in nondiabetic heart failure patients.…”
Section: Albuminuria In Patients With Established Heart Failurementioning
confidence: 99%
“…Despite the high prevalence of microalbuminuria in heart failure, only two studies have prospectively studied the relationship between albuminuria and clinical outcomes in heart failure patients (Table 2) [42,43 ].…”
Section: Albuminuria In Patients With Established Heart Failurementioning
confidence: 99%
“…Furthermore, endothelial dysfunction also plays a role in favoring inflammation and thrombosis via upregulation of adhesion molecules and generation of chemokines. Endothelial dysfunction has been implicated in the pathophysiology of hypertension (63), coronary artery disease (159), chronic heart failure (104), peripheral artery disease (64), diabetes (92), and chronic renal disease (144). …”
Section: Renal Circulationmentioning
confidence: 99%
“…For example, individuals carrying blood group O are associated with low VWF levels (77±27 U/dL), which was recently shown to be attributable to a shorter VWF survival [64], whereas higher VWF levels (137±34 U/dL) are linked to the AB blood group [65]. In diabetics, VWF levels are higher (120 U/dL) than in non-diabetics (89 U/dL) [66]. Since almost all acute coronary syndromes result from arterial thrombus formation after plaque rupture in diseased arteries and since VWF has a pivotal role in thrombus build-up, it seems logic to suspect that high plasma VWF levels might contribute to the pathogenesis of cardiovascular disease (CVD).…”
Section: Is Vwf a Marker For Cardiovascular Disease?mentioning
confidence: 95%